Factors Related to Hospital Bankruptcy: 2007-2019 - Carroll, Nathan W.; Landry, Amy Yarbrough; Erwin, Cathleen O.; Cendoma, Philip J.; Landry, III, Robert J. (Journal of Accounting and Finance, 2021)
From 2007 through 2019 the hospital industry underwent significant changes including the Great Recession and the passage of the Affordable Care Act. Healthcare organizations faced challenges that contributed to a number of alarming trends. Throughout this period, 48 hospitals and health systems filed for bankruptcy protection. Half of these hospitals eventually ceased operations. This article examines factors associated with hospitals that file bankruptcy. Non-financial factors associated with bankruptcy filings were identified from a literature review of hospital trade publications and other available sources. Poor financial management, challenges related to payer mix and reimbursement, and poor management were the most common factors that filing hospitals faced. A comparison between these results and similar research examining the period from 2000-2006 reveals that most of the non-financial factors contributing to bankruptcy are relatively stable over time. These findings emphasize that hospital managers and boards must evaluate the financial health of their organizations using a broad framework that includes political and economic factors as well as financial characteristics.